Virus-like particle vaccines: a prospective panacea against an avian influenza panzootic - Ninyio, Nathaniel Nyakaat; Ho, Kok Lian; Omar, Abdul Rahman; Tan, Wen Siang; Iqbal, Munir; Abdul Razak, Mariatulqabtiah (Multidisciplinary Digital Publishing Institute, 2020)
Epizootics of highly pathogenic avian influenza (HPAI) have resulted in the deaths of millions of birds leading to huge financial losses to the poultry industry worldwide. The roles of migratory wild birds in the harbouring, mutation, and transmission of avian influenza viruses (AIVs), and the lack of broad-spectrum prophylactic vaccines present imminent threats of a global panzootic. To prevent this, control measures that include effective AIV surveillance programmes, treatment regimens, and universal vaccines are being developed and analysed for their effectiveness. We reviewed the epidemiology of AIVs with regards to past avian influenza (AI) outbreaks in birds. The AIV surveillance programmes in wild and domestic birds, as well as their roles in AI control were also evaluated. We discussed the limitations of the currently used AI vaccines, which necessitated the development of a universal vaccine. We evaluated the current development of AI vaccines based upon virus-like particles (VLPs), particularly those displaying the matrix-2 ectodomain (M2e) peptide. Finally, we highlighted the prospects of these VLP vaccines as universal vaccines with the potential of preventing an AI panzootic.